2017
DOI: 10.1136/neurintsurg-2016-012939.rep
|View full text |Cite
|
Sign up to set email alerts
|

Republished: Rete mirabile associated with pial arteriovenous fistula: imaging features with literature review

Abstract: A rete mirabile is a vascular network of intercommunicating small arteries or arterioles that replace the definitive adult artery supplying the brain. It supplies the brain in lower mammals but is not seen in normal human embryological development. A 26-year-old man presented with worsening tinnitus that was interfering with his sleep. On CT and digital subtraction angiography he was found to have a temporal lobe pial arteriovenous fistula with bilateral carotid and vertebral rete mirabile. The patient was off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, true prevalence and what percentage becomes symptomatic are currently unknown. RM has been identified in patients with haemorrhagic or ischaemic manifestations 24 25. In a 2015 review, 34% of the identified RM cases (12/35) presented with SAH,24 the first of which was reported in 1967 26.…”
Section: Discussionmentioning
confidence: 99%
“…However, true prevalence and what percentage becomes symptomatic are currently unknown. RM has been identified in patients with haemorrhagic or ischaemic manifestations 24 25. In a 2015 review, 34% of the identified RM cases (12/35) presented with SAH,24 the first of which was reported in 1967 26.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons that concomitant cerebrovascular diseases are associated with carotid RM are unclear. Currently, these combinations are thought to arise from congenital embryonic etiologies [11]. Therefore, congenital etiology may also be the reason that carotid RM was associated with a moyamoya-pattern collateral vessels of the PCA in our case.…”
Section: Discussionmentioning
confidence: 72%
“…A rete mirabile can be associated with a cerebral aneurysm, spinal aneurysm, carotid-cavernous fistula, pial arteriovenous fistula, AVM, vein of Galen aneurysmal malformation, pseudoxanthoma elasticum, PHACE (posterior fossa anomalies, hemangioma, arterial anomalies, cardiac anomalies, and eye anomalies) syndrome, vertebral artery stenosis, and Dieulafoy's ulcer. 3,6,7,12,14,23 Previous reports have shown that a rete mirabile was associated with cerebral aneurysms in 20% of cases. 3 Hemodynamic stress from complex vessel architecture of the rete mirabile may induce flow-related aneurysm formation.…”
Section: Observationsmentioning
confidence: 98%